Impact of salt and the osmoprotective transcription factor NFAT‐5 on macrophages during mechanical strain. Issue 1 (11th October 2020) - Schröder, Agnes; Leikam, Alexandra; Käppler, Paul; Neubert, Patrick; Jantsch, Jonathan; Neuhofer, Wolfgang; Deschner, James; Proff, Peter; Kirschneck, Christian
Abstract: Myeloid cells regulate bone density in response to increased salt (NaCl) intake via the osmoprotective transcription factor, nuclear factor of activated T cells‐5 (NFAT‐5). Because orthodontic tooth movement (OTM) is a pseudoinflammatory immunological process, we investigated the influence of NaCl and NFAT‐5 on the expression pattern of macrophages in a model of simulated OTM. RAW264.7 macrophages were exposed for 4 h to 2 g cm −2 compressive or 16% tensile or no mechanical strain (control), with or without the addition of 40 mm NaCl. We analyzed the expression of inflammatory genes and proteins [tumor necrosis factor (TNF), interleukin (IL)‐6 and prostaglandin endoperoxide synthase‐2 ( Ptgs‐2 )/prostaglandin E2 (PG‐E2)] by real‐time‐quantitative PCR and ELISA. To investigate the role of NFAT‐5 in these responses, NFAT‐5 was both constitutively expressed and silenced. Salt and compressive strain, but not tensile strain increased the expression of NFAT‐5 and most tested inflammatory factors in macrophages. NaCl induced the expression of Ptgs‐2 /PG‐E2 and TNF, whereas secretion of IL‐6 was inhibited. Similarly, a constitutive expression of NFAT‐5 reduced IL‐6 expression, while increasing Ptgs‐2 /PG‐E2 and TNF expression. Silencing of NFAT‐5 upregulated IL‐6 and reduced Ptgs‐2 /PG‐E2 and TNF expression. Salt had an impact on the expression profile of macrophages as a reaction to compressive and tensile strain that occur during OTM. This was mediated via NFAT‐5, which surprisingly also seems to play a regulatory role in mechanotransduction of compressive strain. Sodium accumulation in the periodontal ligament caused by dietary salt consumption might propagate local osteoclastogenesis via increased local inflammation and thus OTM velocity, but possibly also entail side effects such as dental root resorptions or periodontal bone loss. Abstract : In this study, we showed that salt has an impact on the expression profile of macrophages as a reaction to compressive and tensile strain that occur during orthodontic tooth movement. This effect was mediated via nuclear factor of activated T cells‐5 (NFAT‐5), which seems to play a regulatory role in mechanotransduction of compressive strain. See also News and Commentary by Sweet et al